2021
DOI: 10.1093/cid/ciab533
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcomes Associated With Infective Endocarditis in Pregnancy

Abstract: Introduction Infective endocarditis (IE) is a rare but serious infection complicating pregnancy. Little is known about IE management and outcomes in this population. Methods The National Readmissions Database was used to obtain data between October 2015 and October 2018. Billing codes identified admissions for IE in female patients of reproductive age. Demographic characteristics, comorbidities, and outcomes were compared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…We also observed a high preterm delivery rate, with average gestational age at live birth of 32 weeks, similar to reported literature. 5 This led to further neonatal complications with half of the neonates requiring ICU admissions and prolonged lengths of stay. There were substantial rates of low fetal birth weight, low APGAR scores, respiratory distress syndrome, and intraventricular hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed a high preterm delivery rate, with average gestational age at live birth of 32 weeks, similar to reported literature. 5 This led to further neonatal complications with half of the neonates requiring ICU admissions and prolonged lengths of stay. There were substantial rates of low fetal birth weight, low APGAR scores, respiratory distress syndrome, and intraventricular hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“… 3 In addition, more than half of deliveries complicated by endocarditis are pre-term with an average gestational age of 32.4 weeks, with further morbidity associated with prematurity. 5 While maternal outcomes from cardiac surgery are reportedly similar to non-pregnant women, current literature on management is limited to case series and retrospective reviews and data on neonatal outcomes have not been characterized. 3 , 6 , 7 Discussions regarding indications and timing of valve surgery are particularly complex given poor fetal outcomes with cardiopulmonary bypass.…”
Section: Introductionmentioning
confidence: 99%
“…The DD/Seizures COCs cluster found Diseases of the Endocardium to be the highest non‐pregnancy risk factor, with an OR of 2.53 (1.39, 4.27). Diseases of the endocardium, such as endocarditis, have shown worse maternal and fetal outcomes (Dagher et al, 2021), however, little research has been done on their effect on ASD. The remaining non‐pregnancy related factors associated with the DD/Seizures COCs cluster are also factors for the ASD cohort overall (Grivas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 1 Recent studies reported a maternal mortality rate for IE in pregnancy of 11%, 2 and in-hospital mortality rate during delivery of 17.2%. 3 The timing of and indications for surgical interventions for IE in pregnancy remain controversial. Foetuses with a gestational age (GA) <26 weeks are at a markedly higher risk of mortality and severe morbidities.…”
Section: Discussionmentioning
confidence: 99%